2020
DOI: 10.1111/dth.13416
|View full text |Cite
|
Sign up to set email alerts
|

Successful response to photodynamic therapy with 5‐aminolevulinic acid nanoemulsified gel in a patient with universal alopecia areata refractory to conventional treatment

Abstract: Alopecia areata (AA) is a common autoimmune disease that affects hair follicles and results in nonscarring hair loss. Pathophysiology remains actually unclear. However, genetics and immunity are confirmed as the most important contributors to disease. From the clinical point of view, AA is most often limited to a certain area in the form of alopecic plaques, but it can develop as a total loss of hair on the scalp (AA totalis) or it can even affect the entire body surface (AA universalis), causing a great psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…PDT is a minimally invasive procedure that is clinically used in the treatment of several oncologic human diseases, such as skin, esophageal, head and neck, lung, and bladder cancers [ 57 ]. However, PDT also has several non-oncologic applications [ 58 ], including the treatment of non-cancerous human diseases, such as dermatologic (acne [ 59 ], warts [ 60 ], photoaging [ 61 ], psoriasis [ 62 ], vascular malformations [ 63 ], hirsutism [ 64 ], keloid [ 50 ], and alopecia areata [ 65 ]), ophthalmologic (central serous chorioretinopathy [ 66 ] and corneal neovascularization [ 67 ]), cardiovascular (atherosclerosis [ 68 ] and esophageal varix [ 69 ]), dental (oral lichen planus [ 70 ]), neurologic (Alzheimer’s disease [ 71 ]), skeletal (rheumatoid arthritis [ 72 ]), and gastrointestinal (Crohn’s disease [ 73 ]).…”
Section: Applications Of Pdtmentioning
confidence: 99%
“…PDT is a minimally invasive procedure that is clinically used in the treatment of several oncologic human diseases, such as skin, esophageal, head and neck, lung, and bladder cancers [ 57 ]. However, PDT also has several non-oncologic applications [ 58 ], including the treatment of non-cancerous human diseases, such as dermatologic (acne [ 59 ], warts [ 60 ], photoaging [ 61 ], psoriasis [ 62 ], vascular malformations [ 63 ], hirsutism [ 64 ], keloid [ 50 ], and alopecia areata [ 65 ]), ophthalmologic (central serous chorioretinopathy [ 66 ] and corneal neovascularization [ 67 ]), cardiovascular (atherosclerosis [ 68 ] and esophageal varix [ 69 ]), dental (oral lichen planus [ 70 ]), neurologic (Alzheimer’s disease [ 71 ]), skeletal (rheumatoid arthritis [ 72 ]), and gastrointestinal (Crohn’s disease [ 73 ]).…”
Section: Applications Of Pdtmentioning
confidence: 99%
“…The risk of serious adverse events in these studies was comparable to placebo. phototherApy There are reports on the efficacy of UVB 311 nm [95], PUVA and PUVA-turban [96,97], excimer laser (380 nm) [98] as well as photodynamic therapy [99]. UV-based methods (UVB 311, PUVA, UVA1, 308-nm excimer laser) may be considered in selected cases.…”
Section: Rozszerzona Analiza Bezpieczeństwa Inhibitorów Jakmentioning
confidence: 99%
“…Istnieją pojedyncze doniesienia o skuteczności naświetlań UVB 311 nm [95], PUVA i PUVA-turban [96,97], UVA 1 , lasera ekscymerowego emitującego promienie UV 380 nm [98], a także terapii fotodynamicznej [99].…”
Section: Fototerapiaunclassified
“…Although spontaneous regrowth is possible in some patients, many patients, especially patients with severe AA, have no response to the treatments including minoxidil and glucocorticoids. In other words, alopecia can be very refractory in these patients 4–7 . In recent years, with the development in the pathogenesis research of AA, JAK inhibitors have demonstrated promising effectiveness in treating moderate‐to‐severe AA 8 .…”
Section: Introductionmentioning
confidence: 99%
“…words, alopecia can be very refractory in these patients. [4][5][6][7] In recent years, with the development in the pathogenesis research of AA, JAK inhibitors have demonstrated promising effectiveness in treating moderate-to-severe AA. 8 However, few previous studies have focused on the effectiveness of baricitinib in patients who react poorly to other AA therapies.…”
mentioning
confidence: 99%